PENERAPAN MODEL PEMBELAJARAN PBL BERBANTUAN APLIKASI WORDWALL UNTUK MENINGKATKAN KEMAMPUAN BERKOMUNIKASI DAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI CEBONGAN 03 SEMESTER GENAP TAHUN AJARAN 2024-2025: Penelitian Tindakan Kelas - dewi, maulinda; Mawardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This classroom action research aims to improve communication skills and mathematics learning outcomes of fourth-grade students at SDN Cebongan 03 through the Problem-Based Learning model supported by Wordwall. The results showed a significant improvement in both aspects after two cycles of implementation. This model effectively fostered active, enjoyable, and meaningful learning. The percentage of students achieving the “very good” category in both communication skills and learning outcomes increased by 42.3%.